2022
DOI: 10.3389/fonc.2022.939982
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 as a prognostic and predictive biomarker in stage II colorectal cancer: A multicenter cohort study

Abstract: BackgroundThe identification of high-risk population patients is key to the personalized treatment options for the stage II colorectal cancers. The use of proteomics in the prognosis of patients with stage II colorectal cancer remains unclear.MethodsUsing quantitative proteomics, we analyzed proteins that are differentially expressed in the tumor and adjacent normal tissues of 11 paired colorectal cancer patients with and without recurrence selected by a nested case-control design. Of the 21 identified protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The functional consequences of SAMHD1 in cancer development and treatment still require further researches. In the colorectal cancer, high expression SAMHD1 correlated with metastasis [ 30 ] and indicated poor prognosis of stage II patients [ 31 ]. Consistent with our results, Eudald Felip et al found that low expression of SAMHD1 was associated with a positive prognosis in breast, ovarian and non-small cell lung cancer patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional consequences of SAMHD1 in cancer development and treatment still require further researches. In the colorectal cancer, high expression SAMHD1 correlated with metastasis [ 30 ] and indicated poor prognosis of stage II patients [ 31 ]. Consistent with our results, Eudald Felip et al found that low expression of SAMHD1 was associated with a positive prognosis in breast, ovarian and non-small cell lung cancer patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZNF326 was selected as a candidate biomarker based on previous proteomics analyses and literature reviews ( 24 ). Briefly, we established a Yunnan CRC cohort comprising stage I–III CRC patients at Yunnan Cancer Hospital between December 2010 and February 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with genomics, the verification and interpretation provided by proteomics are closer to phenotype, and virtually all existing drug targets are proteins ( 22 , 23 ). We have previously reported that at least 5 proteins, including the ZNF326 , varied on the tumor tissues between the recurrence and non-recurrence CRC patients through a nested case-control cohort that combined the proteomics ( 24 ). However, the prognostic value of ZNF326 in stage II CRC patients is unclear.…”
Section: Introductionmentioning
confidence: 99%